Personal, occupational and cardiovascular risk factors associated with elevated blood pressure in Brazilian firefighters: a cross-sectional study - Eliana Zandonade; Fernanda Camargo Damacena; Karla Nívea Sampaio; Igor Magalhães Sales (BMJ Open)
Objective Our study evaluated the prevalence of hypertension in a population of Brazilian firefighters and the association of elevated blood pressure (BP) with personal, occupational, and cardiovascular risk factors.Design This was a cross-sectional study.Setting Our study was based on health inspections of the Military Fire Brigade of the Espírito Santo State, Brazil, performed in 2019.Participants The study participants were 859 male Brazilian firefighters.Outcome measures Data collected included sociodemographic (age, ethnicity, educational level, health insurance coverage), occupational (city of work, type of current activity, main operational activity), lifestyle (smoking and alcohol consumption), and health status (fasting glucose, total cholesterol and triglycerides, blood pressure, and anthropometric composition). All firefighters in the pre-hypertension and hypertension range and/or using antihypertensive medication were considered as having BP above normal, and the association of this outcome with sociodemographic, occupational, lifestyle, and health status variables was analysed by a logistic regression model.Results We found that 45.6% of firefighters presented elevated BP levels. A higher chance of elevated BP was observed for firefighters with high school (1.5; 95% confidence interval (CI) 1.02 to 2.19) and postgraduate (1.54; 95% CI 1.03 to 2.30) educational levels, those self-declared as black (1.98; 95% CI 1.03 to 3.78), those working in countryside cities (ie, locations outside the metropolitan circuit; 2.32; 95% CI 1.14 to 4.71), and those with hypertriglyceridemia (1.92; 95% CI 1.19 to 3.11), hyperglycaemia (1.5; 95% CI 1.01 to 2.22), and central obesity (2.34; 95% CI 1.47 to 3.70).Conclusion We found an association between elevated BP and personal, occupational, and cardiovascular risk factors. Awareness of risk factors may grant implementation of more effective intervention and prevention strategies.